The Influence Of Beauty Influencer, Brand Trust, And Brand Image On Customer Loyalty For Skincare Products On E-Commerce Shopee - Novri Gefri Yanti; Nora Pitri Nainggolan (LPPM Universitas Buddhi Dharma, 2025)
Customer loyalty is the main aspect that companies need to study and pay attention to to retain customers. In encouraging customer loyalty, it is necessary to utilize beauty influencers nowadays because beauty influencers have a large number of followers and have an influence on social media. How a company gets its brand image is what encourages consumers to remain loyal to the company. Paying attention to brand image will have the effect of increasing interest and retaining regular customers by ensuring they can remember the characteristics of the products provided. Brand trust is another aspect that influences consumer loyalty. The higher the customer's trust, the greater the consumer's decision to buy other products or brands. Thus, the aim of this research is to examine the role of beauty influencer variables, brand trust and brand image on customer loyalty. the respondents were the people of Batu Aji. By using the Lemeshow formula to measure the sample size, namely 100 respondents. The sampling method applied in this research is non-probability sampling using a simple random sampling technique. In this research, we apply scale range analysis techniques and multiple linear regression analysis using tools such as SPSS 27 data software. Based on the T test analysis, it can be concluded that beauty influencers have a significant positive influence on customer loyalty; brand trust does not have a significant positive effect on customer loyalty; Brand image has a significant positive influence on customer loyalty.